General Elections 2018 in Pakistan: Contestants, Campaigns, and the Rise of Populist Politics - Sidra Zahir; Asifa Shaukat (Journal of Religion and Society, 2025)
This chapter examines the dynamics of the 2018 General Elections in Pakistan, focusing on the major political contestants, their manifestos, and campaign strategies. The study highlights how electoral competition was shaped by populist rhetoric and shifting public expectations. Five mainstream political parties Pakistan Tehreek-e-Insaf (PTI), Pakistan Muslim League (Nawaz) (PML-N), Pakistan People’s Party (PPP), Muttahida Qaumi Movement (MQM), and Muttahida Majlis-e-Amal (MMA) were analyzed with reference to their organizational structures, promises, and electoral mobilization methods. The chapter finds that PTI’s populist appeal, built around themes of anti-corruption, justice, and welfare, redefined the national political discourse and resonated deeply with youth and middle-class voters. In contrast, the campaigns of PML-N and PPP relied heavily on legacy politics, regional patronage, and development narratives. The analysis reveals that campaign effectiveness was closely tied to social media engagement, leadership image, and issue-based communication rather than traditional vote-bank politics alone. Overall, this chapter concludes that the 2018 General Elections marked a turning point in Pakistan’s political landscape by reinforcing populist strategies as central to electoral success. The interplay of digital mobilization, charismatic leadership, and anti-elite sentiment reshaped the nature of political competition and contributed significantly to PTI’s electoral victory. Keywords: General Elections 2018, Populism, Political Campaigns, PTI, PML-N, PPP, MQM, MMA, Pakistan Politics